(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
In this article, on the basis of the analysis of the specific features of the processes of educational relations organized in educational institutions, to increase the effectiveness of the methodology of educational work in general secondary educational institutions, to meaningfully organize the free time of students outside of the classroom and outside of school, first of all to create a perfect person, the features of the manifestation of the content of education science in students is demonstrated.